ТИЛЛАРНИ ЧОҒИШТИРМА ЎРГАНИШНИНГ ЛИНГВОКУЛЬТУРОЛОГИК ЖИҲАТЛАРИ - Кудайбергенова, С.П. (SCIENCE and SOCIETY, 2023)
This article is about the linguistic and cultural aspects of cross-linguistic learning and the application of the method of comparative language learning. The comparative analysis of languages provides an opportunity to check the semantics of verbs, both cross-linguistic and idioethnic.